2014
DOI: 10.1136/bmjopen-2014-005315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical questions raised by providers in the care of older adults: a prospective observational study

Abstract: ObjectiveTo characterise clinical questions raised by providers in the care of complex older adults in order to guide the design of interventions that can help providers answer these questions.Materials and methodsTo elicit clinical questions, we observed and audio recorded outpatient visits at three healthcare organisations. At the end of each appointment, providers were asked to identify clinical questions raised in the visit. Providers rated their questions based on their urgency, importance to the patient'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…About 50% of the total sample of DIIs were culled solely from instant message archives and yet were not documented in the pharmacist encounter log, suggesting under-documentation. Nevertheless, this study's sample of questions was roughly four times larger than the prior studies assessing general or drug-specific information needs of PCOA [1,9]. While larger samples are desirable, we believe that our sample size provides meaningful results given the number of pharmacists (23) and prescribers (102) involved in this study.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…About 50% of the total sample of DIIs were culled solely from instant message archives and yet were not documented in the pharmacist encounter log, suggesting under-documentation. Nevertheless, this study's sample of questions was roughly four times larger than the prior studies assessing general or drug-specific information needs of PCOA [1,9]. While larger samples are desirable, we believe that our sample size provides meaningful results given the number of pharmacists (23) and prescribers (102) involved in this study.…”
Section: Discussionmentioning
confidence: 94%
“…When interviewed in qualitative studies, physicians and other healthcare practitioners have acknowledged that although medication management for older adults is complex and challenging, it can be optimized through interdisciplinary collaboration with pharmacists [26][27][28]. Moreover, other studies of this subject matter similarly suggested that the majority of drug information needs of PCOAs involve adverse drug reactions and drug selection considerations [1,9]. Our study's findings shed much-needed light on the drug information needs of PCOAs and, moreover, the collaboration that transpires between prescribers and pharmacists in the PACE setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical information needs have been extensively studied by collecting questions from physicians and analyzing them [ 24 44 ]. For patients and the general population, the situation is very different.…”
Section: Introductionmentioning
confidence: 99%